Fra respekt, toleranse og forståelse til et samisk perspektiv. . - Drotningsvik, Hanne (The University of Bergen, 2022)
Sami culture and history was first introduced as a topic in the Norwegian national curricula with Mønsterplanen for grunnskolen 1974. From the late 1980s with the then new curriculum Mønsterplanen for grunnskolen 1987 (M87) up until 2020 with Læreplanverket for Kunnskapsløftet 2020 (LK20), Sami culture and history has been recognized as an important part of the curricula, as well as the Norwegian culture. However, there has been a serious lack of Sami content both in my own schooling and in my teacher education. This, and a report from the Sami Parliament in 2016. Stating that the Norwegian people still has a general lack of knowledge about the Sami people and their history and culture, made me curious about what children are expected to learn at school about the Sami people. If Sami culture and history has been regarded as ‘important’ for the last 40 years, why is there still a general lack of knowledge of this topic among Norwegians? Research has already been done on what children are expected to learn, thus, in wanting to understand this question I found that my starting point instead should be to investigate the reasons for introducing Sami culture and history in the Norwegian national curricula. Therefore, this thesis examines the following question: What is the reasoning for inclusion of Sami content in the national curricula M87 and LK20? The idea being that maybe by trying to answer this question, we could come one step closer to discover why there is a gap in knowledge about the Sami in the general public. To answer this question, I have examined case documents related to the preparation process of the two curricula as well as the final curricula. The documents that are in question are quite comprehensive and dense with information. By analyzing these documents and the final curricula M87 and LK20 I found that the reasons for inclusion of the Sami content was founded on three factors or elements. In M87 it was argued that Sami content was included in the curriculum due to the Sami people’s historical ...